Managing catastrophic loss of sensitive data : a guide for IT and security professionals - Photopoulos, Constantine (Syngress ; Elsevier Science [distributor], 2008)
Offering a structured approach to handling and recovering from a catastrophic data loss, this book will help both technical and non-technical professionals put effective processes in place to secure their business-critical information and provide a roadmap of the appropriate recovery and notification steps when calamity strikes. *Addresses a very topical subject of great concern to security, general IT and business management *Provides a step-by-step approach to managing the consequences of and recovering from the loss of sensitive data. *Gathers in a single place all information about this critical issue, including legal, public relations and regulatory issues.